2017
DOI: 10.1148/radiol.2016160175
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of US for Differentiating Perforated from Nonperforated Pediatric Appendicitis: A Prospective Cohort Study

Abstract: Purpose To prospectively evaluate the diagnostic performance of ultrasonography (US) for differentiating perforated from nonperforated pediatric appendicitis and to investigate the association between specific US findings and perforation. Materials and Methods This HIPAA-compliant study had institutional review board approval, and the need for informed consent was waived. All abdominal US studies performed for suspected pediatric appendicitis at one institution from July 1, 2013, to July 9, 2014, were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 21 publications
(25 reference statements)
2
42
2
2
Order By: Relevance
“…Ultrasound is the most commonly used imaging method for diagnosis of acute appendicitis. However, in the differentiation of simple and perforated appendicitis, it is reported that the specificity of ultrasound is high, but its sensitivity is low [9,10] . There are several studies on the diagnostic value of laboratory tests performed to differentiate perforated appendicitis from simple appendicitis.…”
Section: Original Articlementioning
confidence: 99%
“…Ultrasound is the most commonly used imaging method for diagnosis of acute appendicitis. However, in the differentiation of simple and perforated appendicitis, it is reported that the specificity of ultrasound is high, but its sensitivity is low [9,10] . There are several studies on the diagnostic value of laboratory tests performed to differentiate perforated appendicitis from simple appendicitis.…”
Section: Original Articlementioning
confidence: 99%
“…The studies reviewed (Table 1) show that ultrasound has high specificity ranging from 90% to 100%, but low sensitivity ranging from 23% to 44% to distinguish perforated paediatric appendicitis (Table 2) 39,40,42,43 and indicate that the use of a scoring system may be beneficial (Table 3). 42 Sonographic findings with high specificity but low sensitivity to differentiate perforated from non-perforated paediatric appendicitis include the presence of an abscess 7,38 loculated or complex intraperitoneal fluid, 38,43 the presence of an appendicolith, 7,38 dilated bowel 38 and wall thickening of the terminal ileum 43 (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…3 The literature explores the diagnostic performance and findings of ultrasound for differentiating perforated from non-perforated paediatric appendicitis and demonstrates that ultrasound is a useful first-line imaging choice to exclude perforated appendicitis in children. 7,[38][39][40]42,43 4.1 | Diagnostic performance of ultrasound…”
Section: Discussionmentioning
confidence: 99%
“…2) виявлений у 27 (27,8%) дітей, яких оперували з приводу гострого апендициту, а при перфоративному апендициті його виявили у 11 (37,9%) пацієнтів. Тоді як дані літератури свідчать, що наявність копроліту (апендиколіту) є одним із чинників перфорації відростка [4,15], а за даними E. Blumfield та співавт. (2013), наявність апендиколіту у дітей молодше 8 років має чутливість 68% і специфічність 92% щодо наявності перфоративного апендициту [3].…”
Section: результати дослідження та їх обговоренняunclassified